Comparison of Long-Term Effect Between Direct and Indirect Bypass for Pediatric Ischemic-Type Moyamoya Disease: A Propensity Score-Matched Study - Zhao, Yahui; Lu, Junlin; Yu, Shaochen; Li, Jiaxi; Deng, Xiaofeng; Zhang, Yan; Zhang, Dong; Wang, Rong; Wang, Hao; Zhao, Yuanli (Frontiers in Neurology, 2019)
Objectives: This study aimed to compare the postoperative risks and long-term effects between direct bypass surgery (DB) and indirect bypass (IB) surgery for pediatric patients with ischemic-type moyamoya disease (MMD). Method: Pediatric patients (under or equal to 18 years old) who were diagnosed as MMD and given surgical treatments at our center between 2009 and 2015 were retrospectively reviewed from a prospective database. Pediatric hemorrhagic-type MMD patients and those who did not undergo digital subtraction angiography were excluded. Patients who underwent DB were matched with patients who underwent IB using 1:1 propensity score matching. Postoperative complications, recurrent ischemic stroke events and modified Rankin Scale (mRS) scores at the last follow-up were compared between the matched pairs. Results: A total of 223 pediatric patients were screened, and 138 patients (DB:34, IB:104) were considered for the propensity score match. 34 pairs were obtained. Nine patients had postoperative complications, including 6 (17.6%) in the DB group and 3 (8.8%) in the IB group (P=0.476). The mean follow-up period was 71.9±22.2 months for the DB group and 60.2±24.3 months for the IB group (P=0.041). Kaplan-Meier analysis showed a longer stroke-free time in the DB group than in the IB group (P=0.025). At last follow-up, good neurological status (mRS ≤1) was achieved in 32 (94.1%) of the DB group and 34 (100.0%) of the IB group. MRS score at last follow-up were significantly lower than at time of admission (all pts: 1.09±0.45 vs 0.28±0.51, P<0.001; DB group: 1.12±0.48 vs 0.32±0.59, P<0.001; IB group: 1.06±0.42 vs 0.24±0.43, P<0.001).